The course of God's providence : religion, health, and the body in early America - Koch, Philippa (North American religions., 2021)
"This book tells the story of religion and medicine in the eighteenth-century Atlantic world. It rejects simplistic frameworks of secularization and enlightenment and emphasizes, instead, continuing and powerful Protestant ideas of God's oversight in shaping and motivating human activity in the realms of narrative, medicine, missions, charity, and maternity"--